2005
DOI: 10.1176/appi.ajp.162.12.2276
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Posttraumatic Stress Symptoms From Pretraumatic Risk Factors: A 2-Year Prospective Follow-Up Study in Firefighters

Abstract: These results suggest that specific personality traits may constitute markers of vulnerability to the development of psychopathological symptoms after trauma exposure. Early identification of preexisting risk factors is needed to provide effective prevention and intervention for individuals who are at risk of developing trauma-related disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
217
1
16

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(256 citation statements)
references
References 105 publications
20
217
1
16
Order By: Relevance
“…A recent prospective study conducted on firefighter training graduates found that high levels of hostility and low levels of selfefficacy at baseline (before exposure to traumatic on-thejob events) related to PTSD symptoms 2 years later [70]. Results are consistent with those from earlier studies establishing associations between high hostility and anger, reduced self-efficacy, and PTSD and further suggest that these characteristics are factors that predict PTSD [71][72][73][74][75][76][77].…”
Section: Predictive Factorssupporting
confidence: 80%
“…A recent prospective study conducted on firefighter training graduates found that high levels of hostility and low levels of selfefficacy at baseline (before exposure to traumatic on-thejob events) related to PTSD symptoms 2 years later [70]. Results are consistent with those from earlier studies establishing associations between high hostility and anger, reduced self-efficacy, and PTSD and further suggest that these characteristics are factors that predict PTSD [71][72][73][74][75][76][77].…”
Section: Predictive Factorssupporting
confidence: 80%
“…Eber (1991), who reported on several large scale studies of police applicants, indicated that the most important finding was an unambiguous personality profile characterised by high scores on self discipline and tough poise and low on anxiety. Heinrichs, Wagner, Schoch, Soravia, Hellhammer, and Ehlert (2005) indicated that certain aspects of personality may have contributed to the development of mental health symptoms after exposure to trauma in a sample of professional firefighters. High scores on hostility and low scores on self-efficacy were strong predictors of mental health symptoms in this group.…”
mentioning
confidence: 99%
“…Family instability, academic difficulties, a childhood history of abuse and neglect, a history of mental illness and illicit drug use are pre-trauma risk factors that have to be considered in the development of PTSD, but they ostensibly have less effect than exposure to the critical incident itself (O'Brien, 1998:97-98). Heinrichs, Wagner, Schoch, Soravia, Hellhammer and Ehlert (2005:2276-2277 support O'Brien's views as they state that specific personality traits may constitute markers of vulnerability to the development of psychopathological symptoms after trauma exposure. They elaborate on this by specifying the importance of early identification of pre-existing risk factors to provide effective prevention for individuals at risk.…”
Section: Risk Factors In Traumatisation As a Results Of A Critical Incmentioning
confidence: 99%